Family functioning and personal growth in Italian caregivers living with a family member affected by schizophrenia: Results of an add-on study of the Italian network for research on psychoses - Roncone, Rita; Giusti, Laura; Bianchini, Valeria; Casacchia, Massimo; Carpiniello, Bernardo; Aguglia, Eugenio; Altamura, Mario; Barlati, Stefano; Bellomo, Antonello; Bucci, Paola; Cascino, Giammarco; Concerto, Carmen; et al. (Frontiers in Psychiatry, 2023)
To date, the role of family members in caring for relatives affected by schizophrenia has focused largely on the negative aspects of impact of the illness. The present study aimed to: (1) assess family functioning and burden of care in caregivers living in Northern, Central, and Southern Italy who looked after subjects affected by chronic schizophrenia; (2) evaluate the relationship between aspects of family functioning and burden of care, in particular personal growth (PG) of caregivers; and (3) identify variables capable of affecting PG of caregivers. A total of 136 caregivers (mean length of illness of family member more than 20 years) were recruited from 9 Italian research sites and evaluated in terms of “positive” family functioning–problem-solving, communication skills and personal goals Family Functioning Questionnaire (FFQ), burden of care, and PG Family Problems Questionnaire (FPQ). Caregivers reported an overall good family functioning with a relatively low objective and subjective burden of care. The latter was positively correlated with length of illness, with women showing a higher subjective burden than men. Reduced problem-solving skills and ability of each family member to pursue personal goals were both associated with reduced objective and subjective burden which, conversely, were both increased by inadequate support and scarce positive comments from relatives and friends. Approximately 50% of caregivers stated that “they had learned something positive from the situation,” highlighting a statistically higher proportion of caregivers in southern Italy than in northern and central Italy. Caregivers’ PG was associated with good family functioning, adequate professional support, and positive comments. PG also seemed to be positively influenced by support from relatives and friends (O.R. 14.306). The numerous challenges and positive aspects associated with caregiving should be duly acknowledged by mental health services and integrated into routine clinical assessment and intervention framework.